MEMBUKA PASAR PRODUK ENTREPRENEURSHIP BERBASIS SORGUM DI KALANGAN KAUM MUDA TERPELAJAR - Endang Noerhartati; Diana Puspitasari; Endang Retno Wedowati (Jurnal Berdaya Mandiri, 2021)
Developing an entrepreneurial spirit and motivation to produce graduates who can create jobs must be done continuously through an education program, starting from high school to the younger generation of educated people, continuing to tertiary institutions. One of the potential entrepreneurial products is sorghum as an alternative food. The purpose of the activity is to foster an entrepreneurial spirit, increase knowledge about digital-based alternative food sorghum, create the next generation that can increase food diversification based on sorghum, and support the Food National self-reliance. The implementation method begins with preparing sorghum materials and products, materials, and preparation of online activities. Continued implementation, evaluation of activities, reporting, and publication. Participants are students of SMA GIKI 2 Surabaya. The results of the action: participating students understand the concept and development of entrepreneurship in the industrial era 4.0, identify new business development, develop motivation and organize entrepreneurship, and develop sorghum products as alternative food and various entrepreneurial products, business strategies in the industrial era 4.0, business feasibility studies, and can develop entrepreneurial and profitable work plans.